Molecular Typing of Bacterial Pathogens Isolated from Air, Non-Living Surfaces and Clinical Sources in Diyala Governorate Using MLST Technique - Maha Mufeed Alwan, Muthanna A. Al-Mahdawi (Pakistan Journal of Medical & Health Sciences, 2023)
The study aimed to isolate and diagnose bacterial species from clean room air samples for caesarean sections, natural childbirth, sterile preterm infants halls and the sub-corridors leading to these halls and main corridors of the hospital and from the air outside hospital building with isolation and diagnosis of bacterial species from non- living surface and clinical samples that were withdrawn from inside Al-Zahra Hospital for Women and Children in AL-Muqdadiya district in Diyala Governorate – Iraq that extends at latitudes (-3.33 and -36.6) north and longitudes (-44.22 and 45.56) east, during the period from 25 December 2021 to 19 February 2022 in light of the lack of studies that are concerned with this aspect, as 192 air samples were taken distributed to the hospital halls, such as the surgery hall and its sub-corridor leading to it, the delivery hall and its sub-corridor leading to it, the sterile preterm infant unit and its sub-corridor leading to it, the main corridor of these halls, and the air outside the hospital environment, where the air samples distributed into two groups, the first included 96 samples collected in the morning before the start of work at 8 am and the second also included 96 samples collected during Work (noon) at 12 noon ; also, 208 different swabs were collected from patients included 85 swabs after surgeries (caesarean section after suture lift after 7-10 days after delivery), 60 vaginal swabs from patients inside the delivery hall and 63 swabs from newborns lying inside the sterile preterm hall. Also, swabs were collected from non-living surfaces amounting to 100 swabs withdrawn from the natural delivery bed, caesarean section, floors, ventilation outlets, anesthesia device, fluid withdrawal device, incubators for preterm infants, ventilator and dressing cart. The total number of samples withdrawn by the effective method using the SAS air sampling device was 192, with 24 samples for each site, of which 172 samples were given a positive growth rate of 89.5%, the gram-positive bacteria constituted 69%, while the gram-negative bacteria formed an isolation rate of 31%. Sixty vaginal swabs were collected from women in the delivery hall during the examination before the birth began, 33 swabs gave a positive growth rate of 55%, of which 33 were bacterial isolated, the gram negative bacteria formed the isolates by 69.7%. 63 swabs were taken from newborns in the neonatal unit (either normal or caesarean section), those who were admitted to the preterm care hall as a result of complications during childbirth (suffering from shortness, rapid breathing and high bile in the first place, and from inflammation of the respiratory tract and urinary tract infection in the second degree), 38 swabs gave a positive growth rate of 63.3%, of which 38 bacterial isolates were mostly gram-negative bacteria. 85 swabs were taken from caesarean section wounds (7-10 days after caesarean section when the suture is lifted), 29 swabs gave a positive growth rate of 34%, the majority of which were 75.7% gram-negative bacteria. Twenty-six surface swabs gave a positive growth with a rate of 26%, of which 26 different bacterial isolates. The data of the bacterial typing analysis of the three strains of E. coli (multi-resistant bacteria) used in the molecular study by using MLST technique by using housekeeping genes showed that they are globally registered strains on the site of the Institute Pasteur in France, as the results showed that two bacterial isolates, which bear numbers (17,119) of air samples and clinical samples respectively, belong to the same strain (sequence type (ST)=741), while isolates No. (72) of surface samples belong to a different strain (ST=390). Molecular typing (MLST) was performed on three isolates of K. pneumonia (multi-resistant bacteria) where housekeeping genes were used for the purpose of testing. The strains obtained are new strains that have not been isolated before in Iraq, which means that our isolates are not registered in the MLST database at the Institute Pasteur in France.